Snow on Rayado (Rayado, New Mexico Raton Range, 1992)
Article on snow in Rayado, New Mexico
Mater List Item # 3
File location is in the New Mexico File Cabinets
Keywords: Knights of Columbus; Snow; Christmas tree; Boy scouts; Rayado, New Mexico